Analysis of Language Style in Widodari Song by Denny Caknan: A Stylistic Study - Farazila, Nurya; Werdiningsih, Yuli Kurniati (Universitas PGRI Semarang, 2024)
This study aims to 1) describe the use of language style in a Javanese song entitled Widodari by Denny Caknan 2) Describe the meaning expressed in the Widodari song by Denny Caknan. Denny Setiawan or Denny Caknan is considered successful in inspiring the millennial generation to be culturally literate through their musical works with regional nuances. Denny became known to the public when his song, entitled Kartonyono Medhot Janji, went viral in 2019. In early 2021 Denny released a new song entitled Widodari with Guyon Waton. This song was created due to the breakup of Denny Caknan's relationship with Happy Asmara who is often referred to as his ex-lover, now the song has been uploaded on the YouTube channel and has been watched more than 30 million times. According to Denny Caknan and Guyon Waton, the language used in the Widodari song is almost extinct among Javanese today, so that today's generation of children recognize the Widodari language again. Widodari in Indonesian means Bidadari this song talks about someone who is in love after seeing or meeting a woman who he believes can heal his heart that was once hurt. The study used is Stylistics which focuses on the use of assonance, alliteration, repetition, and simploke language styles, and meanings in a Widodari song. The method used is descriptive analysis. Research data in the form of words, sentences, and quotes in the song. The source of this research comes from recordings in the form of MP3 from the results of downloading on the internet to search for songs created by Denny Caknan. Then draw conclusions.